Analgesic dorsal root ganglion field stimulation blocks both afferent and efferent spontaneous activity in sensory neurons of rats with monosodium iodoacetate-induced osteoarthritis. Issue 11 (November 2022) - Chao, D.; Tran, H.; Hogan, Q.H.; Pan, B.
Summary: Objectives: Chronic joint pain is common in patients with osteoarthritis (OA). Non-steroidal anti-inflammatory drugs and opioids are used to relieve OA pain, but they are often inadequately effective. Dorsal root ganglion field stimulation (GFS) is a clinically used neuromodulation approach, although it is not commonly employed for patients with OA pain. GFS showed analgesic effectiveness in our previous study using the monosodium iodoacetate (MIA) - induced OA rat pain model. This study was to evaluate the mechanism of GFS analgesia in this model. Methods: After osteoarthritis was induced by intra-articular injection of MIA, pain behavioral tests were performed. Effects of GFS on the spontaneous activity (SA) were tested with in vivo single-unit recordings from teased fiber saphenous nerve, sural nerve, and dorsal root. Results: Two weeks after intra-articular MIA injection, rats developed pain-like behaviors. In vivo single unit recordings from bundles teased from the saphenous nerve and third lumbar (L3) dorsal root of MIA-OA rats showed a higher incidence of SA than those from saline-injected control rats. GFS at the L3 level blocked L3 dorsal root SA. MIA-OA reduced the punctate mechanical force threshold for inducing AP firing in bundles teased from the L4 dorsal root, which reversed to normal with GFS. After MIA-OA, there was increased retrograde SA (dorsal root reflex), which can be blocked by GFS. Conclusions: These results indicate that GFS produces analgesia in MIA-OA rats at least in part by producing blockade of afferent inputs, possibly also by blocking efferent activity from the dorsal horn.